EFFECTIVE CONDITIONS OF MOISTURE CONTENT, INOCULUM RATE, AND MEDIUM COMPOSITION FOR THE PRODUCTION OF CELLULASE, AMYLASE, AND XYLANASE BY FERMENTATION OF SLAUGHTERHOUSE RUMEN CONTENTS - S. B. Cho; J. W. Park; S. O. Kim; M. Y. Won; K. K. Park; E. J. Kim; K. H. Kim; Y. K. Oh; S. K. Kim (Journal of Animal and Plant Sciences, 2013)
This study was conducted to investigate the optimum conditions of moisture, inoculum, and medium ingredients, for enzyme production by solid-state fermentation of rumen content, a slaughterhouse by-product, intended to be used as a feed additive. Bacillus pumilus, Bacillus amyloliquefaciens, and Saccharomyces cerevisiae were used as starter cultures. Slaughterhouse rumen content, molasses, cornstarch, soybean meal, wheat bran, and ammonium chloride were selected as the variables of the medium ingredients. Moisture content and inoculum were used as the variables of the fermentation condition. The enzyme activities of cellulase, amylase, and xylanase were assessed using the Taguchi experimental design. Thus, the study was conducted with 18 experimental conditions defined by various combinations of 8 variables. To determine the integrated effects of variables on all 3 enzymes simultaneously, the standardized value of signal-noise (SN) ratio was calculated, following which, the average value of the standardized SN ratios was used to determine the effects of different levels of variables on enzyme activity. In conclusion, the moisture content, molasses, and ammoniumchloride were detected as effective variables with significance (p < 0.05) for the improvement of enzyme production during the fermentation of slaughterhouse rumen content. We found that 40% moisture, 20% rumen contents, 1%inoculum, 10% molasses, 2% cornstarch, 5% soybean meal, 30% wheat bran, and 0.1% ammonium chloride of total fermentation medium were found to be the effective levels of variables for the simultaneous production of the three enzymes that were assessed. This is the first study to report the development of the feed additive containing various enzymes produced by recycling of rumen contents, a slaughterhouse by-product.
Keywords: Rumen contents; Fermentation; Cellulase; Amylase; Xylanase; Taguchi method